Dust deposition characteristics on photovoltaic arrays investigated through wind tunnel experiments - Juan Wang; Weiwei Hu; Yunyun Wen; Fei Zhang; Xingcai Li (Scientific Reports)
Abstract Optimizing the installation parameters of photovoltaic panels in a photovoltaic array to reduce dust accumulation, thereby enhancing their power generation, is a crucial research topic in the construction of solar power stations in desert regions. Utilizing a series of wind tunnel experiments on a photovoltaic array comprising four equally sized panels, this study assessed how variations in tilt angle, mounting height, spacing, and incoming flow direction influence both the accumulation mass of dust and the particle size distribution in a photovoltaic array. The results indicate that the dust accumulation on the first panel exponential growth with increasing tilt angle, incoming flow angles, and height, while subsequent panels displayed a trend of initial increase followed by a decrease, with a maximum increasing ratio achieved at specific installation configurations, the difference of dust mass on each panel can even be several times. Notably, when the spacing between panels exceeds twice the panel height, the mutual influence on dust deposition becomes negligible, providing a quantifiable threshold for optimal panel spacing. Additionally, significant differences exist in the particle size characteristics of dust in the panel of the array, influenced by the installation parameters of panels and the direction of the incoming flow. This research not only enhances the understanding of dust accumulation in solar energy systems but also offers practical recommendations for optimizing installation strategies, thereby improving the economic viability of solar power stations, particularly in desert regions.